Work Engagement of PT SPSR’s Employees in Relation to Work Load and Work Discipline - Nursanti, Tinjung Desy; Guna, Adhi (Dynamic Management Journal, 2025)
The concept of work engagement is of paramount importance for organizations, since it represents the degree of emotional connection and dedication that employees exhibit towards their work. This phenomenon is distinguished by the manifestation of affirmative energy, fervor, unwavering focus, and a perception of being motivated while engaging in designated duties. The purpose of this study is to investigate the level of work engagement at PT SPSR and see if it is influenced by workload or work discipline. This study is classified as a population study as it has a sample size of 56 permanent employees from PT SPSR who were selected as research respondents. Data is collected through the administration of questionnaires using the Google Form platform. The chosen analytical approach involves the utilization of Structural Equation Modeling (SEM) with the implementation of the SmartPLS 4 methodology. The utilization of this approach can be attributed to the constrained pool of participants and the need to streamline the procedure by eliminating the need for traditional assumption testing. The results suggest that there exists a non-significant and inverse correlation between workload and work engagement. On the contrary, there exists a robust and statistically significant correlation between work discipline and job engagement.